Pengaruh Kepemimpinan Transformasional dan Komitmen Organisasi terhadap Kepuasan Kerja Karyawan dan Organizational Citizenship Behavior (OCB) pada Baleka Resort Hotel & Spa Legian - Suryanatha, A.A. Ngr. Bayu; Ardana, Komang (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
The purpose of this study was to determine the direct effect of transformational leadership and organizational commitment on job satisfaction and organizational citizenship behavior. Research located at Baleka Resort Hotel & Spa Legian, with a sample of 70 people. Analysis techniques are used path analysis. Test path analysis showed a positive effect of transformational leadership and significant impact on job satisfaction, organizational commitment and a significant positive effect on job satisfaction, transformational leadership and significant positive effect and indirectly through job satisfaction on OCB, organizational commitment and significant positive effect and indirect through job satisfaction on OCB, and job satisfaction and a significant positive effect on OCB
Keywords: transformasional leadership, organizational commitment, job satisfaction and organizational citizenship behavior